2016
DOI: 10.1213/ane.0000000000001231
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes for Different Forms of Stress Cardiomyopathy After Surgical Treatment for Subarachnoid Hemorrhage

Abstract: Background Stress-induced cardiomyopathy (SCM) after subarachnoid hemorrhage (SAH) includes predominant apical or basal regional left ventricular dysfunction (RLVD) with concomitant changes in electrocardiogram or increase in cardiac enzymes. We hypothesized that difference in outcome is associated with the type of RLVD after SAH. Methods We studied a single-center retrospective cohort of SAH patients hospitalized between 2000 and 2010 with follow-up until 2013. We classified patients who had an echocardiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…To the best of our knowledge, there are only two studies on long-term complications and cardiac events after SAH [ 22 , 23 ]. Consistent with the present study, they revealed an increased risk of death, especially early on after SAH, and an increased risk of cardiac events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, there are only two studies on long-term complications and cardiac events after SAH [ 22 , 23 ]. Consistent with the present study, they revealed an increased risk of death, especially early on after SAH, and an increased risk of cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…One of these studies was limited by its design as a registry study, with no detailed data regarding which cardiac complications affected each SAH patient [ 22 ]. The other study reported on only the association between stress cardiomyopathy and death [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported by Sugimoto et al the reduction of LV ejection fraction (below 50%) was observed in up to 62% of patients. However, the average LV EF of all patients was approximately 40% [49,51]. A study by Ahmadian et al reported similar prevalence: 55.7% of patients had LV EF between 40-60%, and only 6.6% of patients had LV EF lower than 40% [33].…”
Section: Echocardiographic Left Ventricular Dysfunctionmentioning
confidence: 99%
“…Difficulties to achieve the blood pressure goals for haemodynamic augmentation because of low cardiac output are reported. In this situation, increased doses of inotropes and vasopressors could worsen hypotension and can determine secondary brain injury [51]. When high doses of vasopressors and inotropes are ineffective, the management using IABP may be indicated [56].…”
Section: Neurogenic Stress Cardiomyopathy Treatmentmentioning
confidence: 99%